Functional morphology underlies performance differences among invasive and non-invasive ruderal Rubus species - Caplan, Joshua S.; Yeakley, J. Alan (Springer, 2013)
The ability of some introduced plant species to outperform native species under altered resource conditions makes them highly productive in ecosystems with surplus resources. However, ruderal native species are also productive when resources are available. The differences in abundance among invasive and non-invasive ruderal plants may be related to differences in ability to maintain access to or store resources for continual use. For a group of ruderal species in the Pacific Northwest of North America (invasive Rubus armeniacus; non-invasive R. ursinus, R. parviflorus, R. spectabilis, and Rosa nutkana), we sought to determine whether differences in functional morphological traits, especially metrics of water access and storage, were consistent with differences in water conductance and growth rate. We also investigated the changes in these traits in response to abundant vs. limited water availability. Rubus armeniacus had among the largest root systems and cane cross-sectional areas, the lowest cane tissue densities, and the most plastic ratios of leaf area to plant mass and of xylem area to leaf area, often sharing its rank with R. ursinus or Rosa nutkana. These three species had the highest water conductance and relative growth rates, though Rubus armeniacus grew the most rapidly when water was not limited. Our results suggest that water access and storage abilities vary with morphology among the ruderal species investigated, and that these abilities, in combination, are greatest in the invasive. In turn, functional morphological traits allow R. armeniacus to maintain rapid gas exchange rates during the dry summers in its invaded range, conferring on it high productivity.
Keywords: invasiveness; water relations; fluctuating resources; growth allocation; rubus fruticosus